Immune response to SARS-CoV-2 in health care workers following a COVID-19 outbreak: A prospective longitudinal study - Fill Malfertheiner, Sara; Brandstetter, Susanne; Roth, Samra; Harner, Susanne; Buntrock-Döpke, Heike; Toncheva, Antoaneta A.; Borchers, Natascha; Gruber, Rudolf; Ambrosch, Andreas; Kabesch, Michael; Häusler, Sebastian (Journal of clinical virology, 2020)
Currently, little is known about the progression of an immune response against SARSCoV- 2 upon infection or sub-infection-exposure over time. We examined the serologic response in healthcare workers up to 12 weeks after a well-documented and contained outbreak and compared results with findings from earlier serologic testing in the same population. This study followed 166 health care workers of the University Perinatal Care Center, Regensburg, Germany, for up to 12 weeks. 27 of the subjects had previously tested positive for the presence of SARS-CoV-2 by PCR testing and developed COVID-19. Serologic responses were tested with two independent commercially available test kits. 77.8 % of COVID-19 study subjects developed a specific IgG-response over the course of the 12-week study, while none of the COVID-19 contact groups had a detectable IgG response. Amongst most COVID-19 patients the values of detectable IgG-responses significantly increased over time as confirmed with both tests, while that of positive IgA responses decreased. Between the number of reported symptoms and antibody responses in COVID-19 patients no correlation was found and no new cases of seroconversion were identified in asymptomatic coworkers with negative PCR during the outbreak. Immune response after COVID-19 increases significantly over time but still approximately 22 % of COVID-19 patients did not mount a measurable serologic immune response within 60 days. Exposed co-workers did not develop any relevant antibody levels at all. We conclude that immunity after infection increases over time, but the antibody response does not develop reliably in all infected people.